STUDI TENTANG PENGGUNAAN MEDIA PEMBELAJARAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SMPN5 KOTA KUPANG - Hendrik Jehane (Jurnal Lazuardi, 2019)
ABSTRACT Instructional media is very important to support the scientific-based learning process. The problem of this research is (1) does the Indonesian language teacher in SMPN 5 Kupang City use instructional media in learning Indonesian?; (2) what types of instructional media are used in Indonesian language learning?; (3) is the use of instructional media in accordance with basic competencies and indicators that are set?; (4) how is the creativity of the teacher in designing and using instructional media?; (5) what are the obstacles faced by the teachers in designing and using instructional media? The type of research used is descriptive research. The purpose of descriptive research is to describe a phenomenon as it was at the time of the study. This research approach is a qualitative approach. The result showed that the teachers of SMPN 5 Kupang City used instructional media in learning Indonesian according to minimum standards. The types of instructional media developed and used by teachers in addition to the minimum standard media are images, original objects, the environment, print media, the internet, and the surrounding community. There is still a mismatch between the learning media used with the subject matter being taught. Indonesian language teachers are still not creative enough to design and use instructional media. The lack of electricity and other facilities in school and the lack of mastery of information technology are inhibiting factors for teachers in developing instructional media. The teacher’s effort to overcome the limitations of the instructional media is to use images, original objects, the environment, print media, the internet, and the surrounding community.